The Discovery and Study of the Heterogeneous Texts from the Age of Manuscripts and Transcripts. - CHENG Sudong (Frontiers of History in China, 2025)
In the age of manuscripts and transcripts, text generation can be ascribed to four distinct roles: the author, the narrator, the transcriber, and the scribe. The author is the creator of the text, while the scribe acts as the disseminator. The narrator and transcriber may perform the dual roles. Recognizing the different powers associated with these four roles, particularly how transcribers amalgamate diverse textual sources to produce "heterogeneous" derivative texts provides valuable insights into the text generation process and its underlying structure and literary elements during the age of manuscripts and transcripts. In essence, acknowledging the transcribers' creativity in generating heterogeneous texts and exploring the establishment of a "transcriber studies" paradigm at the methodological level is crucial for advancing in-depth research on texts from the age of manuscripts and transcripts.